GCSE German - Wheeler, Ken; Edited by Courcy, Jayne de (London Harper Collins, 2003)
Each title in this series provides: content coverage for the GCSE specifications; 20-minute revision sessions; "check yourself" questions to test understanding; "A* extra" information boxes for highlighting likely exam questions; and an exam practice chapter with guidance on exam technique.
Include Colored Illustration, Tables and Indexes
Keywords: German language--Examinations -- German language -- General Certificate of Secondary Education